Partisipasi Politik Masyarakat Dalam Pemilihan Gubernur Dan Wakil Gubernur Sumatera Utara 2018 di Desa Selemak Kecamatan Hamparan Perak Kabupaten Deli Serdang - Noverman Halawa; Abdul Kadir; Armansyah Matondang (Universitas Medan Area, 2019)
Related to the political participation of the region which is the location of this study also discusses the problem at the level of political participation in the election of the Governor and Deputy Governor of North Sumatra 2018 is still very low. What causes it needs to be changed so that solutions can be found to overcome it, so this research is very important. This study uses qualitative methods with interview, observation, document and trigulation techniques. Hope the data obtained can be more complete tah facts in the field. The concept used in this study is the concept of Arifin Anwar (2011) which divides three assessments of political participation, namely providing votes in elections, campaigns and lobbying. The problem in this study is the political participation of the society in the election of the Governor and Deputy Governor of North Sumatra 2018, and what factors are Inhibiting the Political Participation of the Society. Based on the research results obtained in the field, it shows that political participation in the community is very low, there are also factors that in volve community participation are internel factors and external factors. Suggestions for the future are expected so that the bureaucracy is neutral in very regional head election implementation, it is also hoped that supervision in the regional head election will be tightened.